Penggunaan Internet dan Peluang Berwirausaha di Indonesia - Nelsi Agustina Siburian; Zuhrinal M. Nawawi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Nowadays, the internet has become a necessity in social and economic life that provides convenience in communication and social interaction. In addition, the presence of the internet supported by advances in digital technology is expected to provide business opportunities. Internet access has become easier with the rapid use of cell phones/mobile phones. This study aims to examine the effect of internet use on entrepreneurship opportunities in Indonesia through descriptive analysis methods and binary logistic regression. This research uses data from the 2019 National Socio-Economic Survey. Entrepreneurs in this research are limited to individuals who seek to be assisted by permanent workers or paid workers in the age range of 25 to 44 years. Of the 348735 samples that became the unit of analysis, there were 7108 who were entrepreneurs or about 2.04 percent. This study found that individuals who use the internet have a higher chance of becoming an entrepreneur than individuals who do not use the internet and this finding is statistically significant. In addition, the level of education significantly affects individuals to become entrepreneurs, but individuals with higher education have a lower tendency to become entrepreneurs than those with high school education and below. Keywords: Internet, Binary Logistics Regression, Entrepreneur